Designing and characterization of bilayer films based on bitter vetch seed protein and polylactic acid for enhanced food packaging - Sona Dodange; Hajar Shekarchizadeh; Mahdi Kadivar (Heliyon)
Packaging films based on natural biopolymers often suffer from inadequate barrier and mechanical properties. To address these challenges, multilayer films have emerged as potential solutions. In this study, we prepared bilayer films using bitter vetch seed protein (BVSP) and polylactic acid (PLA). The barriers, mechanical, physical, chemical, thermal and morphological properties of the prepared films were evaluated. The bilayer films exhibited robust adhesion between the BVSP and PLA layers without any chemical modification or additional components. This physical interaction between the layers contributed to the overall film properties. The addition of the PLA layer to BVSP films led to reduced solubility and moisture content in the bilayer films compared to pure BVSP films. The bilayer films demonstrated good tensile strength, ranging from 13.46 to 15.51 MPa, surpassing the BVSP films (ranging from 5.66 to 6.25 MPa). Additionally, the bilayer films exhibited better elongation at break, ranging from 17.91 % to 27.68 %, compared to pure PLA films (ranging from 14.95 % to 23.28 %). The bilayer films exhibited reduced water vapor permeability (WVP), ranging from 1.40 × 10⁻1⁰ to 6.55 × 10⁻1⁰ g/Pa.s.m, in contrast to the BVSP film (ranging from 1.02 × 10⁻⁹ to 1.57 × 10⁻⁹ g/Pa.s.m). This improvement was attributed to the hydrophobic nature of the PLA layer. Thermal decomposition curves revealed that the BVSP/PLA bilayer film exhibited greater stability than the pure BVSP film. Based on our results, bilayer films with superior properties compared to pure BVSP films are promising candidates for food packaging applications.